2010
DOI: 10.1187/cbe.09-11-0080
|View full text |Cite
|
Sign up to set email alerts
|

Does Displaying the Class Results Affect Student Discussion during Peer Instruction?

Abstract: The use of personal response systems, or clickers, is increasingly common in college classrooms. Although clickers can increase student engagement and discussion, their benefits also can be overstated. A common practice is to ask the class a question, display the responses, allow the students to discuss the question, and then collect the responses a second time. In an introductory biology course, we asked whether showing students the class responses to a question biased their second response. Some sections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 33 publications
(49 reference statements)
6
61
0
5
Order By: Relevance
“…Our research is consistent with the findings of Perez et al [22] and Brooks and Koretsky [21] that displaying the results of the initial voting session can affect students' decision making and confidence during discussion. As predicted by Perez et al [22], the students in our research experience that an alternative with a clear majority of the votes becomes a center of focus for the group discussion, although not in a positive sense.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our research is consistent with the findings of Perez et al [22] and Brooks and Koretsky [21] that displaying the results of the initial voting session can affect students' decision making and confidence during discussion. As predicted by Perez et al [22], the students in our research experience that an alternative with a clear majority of the votes becomes a center of focus for the group discussion, although not in a positive sense.…”
Section: Discussionsupporting
confidence: 93%
“…There have been several recent quantitative studies on different aspects of Peer Instruction [21][22][23][24]. Previous studies have shown that the amount of correct votes increases after the discussion [16,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns trabalhos tiveram como foco elementos específicos do método, focando no(a): tipo de sistema de votação utilizado [100]; tipo de interação que ocorre na etapa de discussão entre os colegas [94,[101][102][103]; importância das atividades préviasàs aulas [87]; tempo de submissão das respostas dos estudantes [104]; apresentação dos resultados da primeira rodada de votação [105,106]; relação entre a localização dos estudantes e a distribuição de repostas [107]. Além disso, um dos trabalhos encontrados nesta revisão almejou construir uma expressão analítica que revela a correlação entre a taxa de acertos, nos Testes Conceituais, dos estudantes antes e após a discussão entre os colegas [108].…”
Section: Pesquisas Referentes Aos Elementos Que Compõem O Piunclassified
“…A pesquisa realizada por Perez et al (2010) retratam a experiência da PI em um curso introdutório de biologia com a utilização de clickers para a votação, além dos resultados positivos com a adoção do método, os autores descobriram que após a primeira votação ao ver no gráfico de barras a resposta mais comum, mesmo sem saber se estava correto, os estudantes tinham a tendência de escolher esta resposta na segunda votação, o que poderia dar uma falsa impressão de melhoria no desempenho da turma, neste sentido a melhor estratégia é a não revelação da porcentagem de cada alternativa escolhida.…”
Section: O Método Peer Instructionunclassified